ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHINDARAN PAJAK PADA PERUSAHAAN SEKTOR PERTAMBANGAN - Sanisahuri Sanisahuri; Saumi Rahmadani; Irsad Irsad (Niagawan, 2022)
This study aims to determine the effect of return on assets and sales growth on tax avoidance in mining companies listed on the Indonesia Stock Exchange for the 2015-2020 period. The research methodology used is a quantitative descriptive method. The type of data used in this research is quantitative data, which is obtained in the form of numbers and numbers. Source of data in the form of secondary data. The sample of this study was selected by purposive sampling technique and obtained as many as 11 companies for 6 periods, namely 2015-2020. The analytical method used is multiple linear regression. The results of the research analysis show that Return on Assets has a significant effect on Tax Avoidance in Mining Sector Companies. The results of the research analysis show that Sales Growth has a significant effect on Tax Avoidance in Mining Sector Companies